Perancangan Dan Pembuatan CMS(Content Management System) E-Commerce Untuk Umum - Arthur Johanes Pello; Adi Wibowo; Lily Puspa Dewi (Jurnal Infra, 2013)
Today more and more online stores in Indonesia, start from self-made online store, and also based on a CMS (Content Management System). Internet facilities are used by people around the world to be able to communicate, get information, and is used as a medium for online trading between companies and business entities with their customers. Trading using internet technology known as E-Commerce (Electronic Commerce).Based on the background, the authors designed and created a CMS (Content Management System) for E-Commerce, where CMS (Content Management System) can be used easily by the company to adopt a system of SaaS (Software as a Service) that can be directly used by internet users who want to market their goods to be marketed.